Performance of full scale embankment with hexagonal wire mesh reinforcement and gabion facing - Somkiat Khwanpruk; Bergado, Dennes T.; Noppadol Phien-Wej; Lin, Der Guey; Royal Thai Government (Bangkok : Asian Institute of Technology, 1998)
This study are focus on field behavior of mechanically stabilized embankment which was carried out on a fully instrumented hexagonal wire mesh reinforcement constructed on soft clay foundation at Asian Institute of Technology campus. The reinforced wall consist of 80 degree gabion cages facing on one side and a sloping umeinforced opposite side with the total height of 5.71 meters. Settlements, pore pressure, lateral movement of subsoil were monitored during and after construction. Laboratory and in-situ test of subsoil foundation were carried out. By observing the lateral movements and settlements. It was observed that the maximum settlement of 0.350 m for 200 days after construction while the settlement prediction by using one-dimensional (Terzaghi, 1947), three-dimensional (Skempton and Bjerrum, 1957), the method proposed by Asaoka (1978) and the water content method (Bergado et al, 1995) were found to be higher than observations which are 579 mm, 522 mm, 448 mm and 576 mm, respectively. The degree of consolidation of the foundation subsoil is 78% at 200 days after construction. The maximum lateral movement was 0.15 m for 200 days after construction that was occurred in foundation soil at 3 to 4 m depth. The maximum excess pore water pressure for both type of hexagonal wire mesh area occur 2.7 and 3.3 t/m 2 at 3 m and 6 m depth, respectively, for 7 days after construction. The external stability was analyzed namely ove1turning, horizontal sliding and bearing capacity. The factor of safety for those stability are 25, 5.6 and 1.2, respectively.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Soil stabilization; Embankments